Analysis of the network pharmacology and the structure-activity relationship of glycyrrhizic acid and glycyrrhetinic acid - Ni, Qingqiang; Gao, Yuxuan; Yang, Xiuzhen; Zhang, Qingmeng; Guo, Baojian; Han, Jinxiang; Chen, Shaoru (Frontiers in Pharmacology, 2022)
Licorice, the herbal product derived from the root of Glycyrrhiza species, has been used as a sweetening agent and traditional herbal medicine for hundreds of years. Glycyrrhizic acid (GL) and glycyrrhetinic acid (GA) are the most important active ingredients in licorice. Both GL and GA have different pharmacological effects against tumors, inflammation, viral infection, liver diseases, neurological diseases and metabolic diseases. However, they also exhibit differences. Upon KEGG analysis, we found that licorice is involved in neuroactive ligand‒receptor interactions, while GA is mostly involved in arrhythmogenic right ventricular cardiomyopathy. In this article, we comprehensively review the therapeutic potential of GL and GA by focusing on their pharmacological effects and working mechanisms. We systemically discuss the structure-activity relationship of GL and GA, as well as their isomers. Based on the various pharmacological activities of GL, GA and their isomers, we proposed further development of structural derivatives of GA after chemical structure modification, with less cytotoxicity but higher targeting specificity. More research is needed on the clinical applications of licorice and its major ingredients.